2015
DOI: 10.1007/s40843-015-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Probing surface hydrophobicity of individual protein at single-molecule resolution using solid-state nanopores

Abstract: Solid-state nanopore is found to be a promising tool to detect proteins and their complexes. Nanopore-protein interaction is a fundamental and ubiquitous process in biology and medical biotechnology. By translocating phi29 connector protein through silicon nitride nanopores, we demonstrate preliminarily probing the surface hydrophobicity of individual protein at single-molecule resolution. The unique "double-level event" observed in the translocation and the ratio of two current drop levels suggest that the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The role of pore-water/protein interaction strength has been studied less till now. The nanopore-protein interaction is complicated, which involves several influencing factors, such as electrostatic force and van der Waals force, etc [23,24]. The corona formation theory can be used to describe the interaction between protein and nanopore based on the protein dwell time in experimental study [1].…”
Section: Introductionmentioning
confidence: 99%
“…The role of pore-water/protein interaction strength has been studied less till now. The nanopore-protein interaction is complicated, which involves several influencing factors, such as electrostatic force and van der Waals force, etc [23,24]. The corona formation theory can be used to describe the interaction between protein and nanopore based on the protein dwell time in experimental study [1].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, silicon nitride (Si 3 N 4 ) nanopores have been proven to be a novel protein sensing platform with excellent physical and chemical stabilities. Many protein molecules have been studied by using solidstate nanopores including lysozyme [44], avidin [44], immunoglobulin G [44], β-lactoglobulin [44], ovalbumin [50], bovine serum albumin [24,39,44,51], β-galactosidase [50], his-tagged proteins [52], mammalian prion protein [44], phi29 connector protein [53], and histidine-containing phosphocarrier protein [50]. Besides, the Meller group has demonstrated that ubiquitin and ubiquitin chains can be efficiently discriminated using Si 3 N 4 nanopores [23].…”
Section: Introductionmentioning
confidence: 99%